Effectiveness of Emotion Regulation Therapy on Suicide Ideation in Mothers of Children with Intellectual Disabilities during the COVID-19 Outbreak: Effectiveness of Emotion Regulation Training on suicide ideation in Caregiver Mothers of Children with intellectual disabilities - Ariapooran, Saeed; Abdolmaleki, Bahram; Shaybani, Hosein (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:COVID-19 has led to many psychological problems in the world. Mothers of children with intellectual disabilities may experience psychological problems, including suicidal ideation in the outbreak of COVID-19.This study aimed to evaluate the effectiveness of emotion regulation therapy (ERT) on suicide ideation among mothers of children with intellectual disabilities. Materials and Methods:The research method was quasi-experimental with experimental and control groups. The statistical population of this study consisted of all mothers of children with severe and profound intellectual disabilities in Razan city. 24 mothers with scores higher than the cut-off point (≥6) for the Beck Suicide Ideation Scale selected by convenience sampling method and were randomly assigned in the experimental and control groups. The ERT was applied for the experimental group in 8 sessions, and the control group did not receive any training during the sessions. Analysis of covariance with repeated measures were used to analyze the data. Results:The results showed that ERT was effective in reducing suicide ideation in caregiver mothers of children with intellectual disabilities (p<0.05). Conclusion:According to the results, the ERT is useful for reducing the suicide ideation in mothers of children with intellectual disabilities. ERT causes mothers to pay attention to their cognitive appraisal after awareness and acceptance of their negative emotions, and suicide ideation will decrease in them.